Screening and management of mental health and substance use disorders in HIV treatment settings in low‐ and middle‐income countries within the global IeDEA consortium. Issue 3 (30th March 2018) - Parcesepe, Angela M; Mugglin, Catrina; Nalugoda, Fred; Bernard, Charlotte; Yunihastuti, Evy; Althoff, Keri; Jaquet, Antoine; Haas, Andreas D; Duda, Stephany N; Wester, C William; Nash, Denis
Abstract: Introduction: Integration of services to screen and manage mental health and substance use disorders (MSDs) into HIV care settings has been identified as a promising strategy to improve mental health and HIV treatment outcomes among people living with HIV/AIDS (PLWHA) in low‐ and middle‐income countries (LMICs). Data on the extent to which HIV treatment sites in LMICs screen and manage MSDs are limited. The objective of this study was to assess practices for screening and treatment of MSDs at HIV clinics in LMICs participating in the International epidemiology Databases to Evaluate AIDS (IeDEA) consortium. Methods: We surveyed a stratified random sample of 95 HIV clinics in 29 LMICs in the Caribbean, Central and South America, Asia‐Pacific and sub‐Saharan Africa. The survey captured information onsite characteristics and screening and treatment practices for depression, post‐traumatic stress disorder (PTSD), substance use disorders (SUDs) and other mental health disorders. Results: Most sites (n = 76, 80%) were in urban areas. Mental health screening varied by disorder: 57% of sites surveyed screened for depression, 19% for PTSD, 55% for SUDs and 29% for other mental health disorders. Depression, PTSD, SUDs and other mental health disorders were reported as managed on site (having services provided at the HIV clinic or same health facility) at 70%, 51%, 41% and 47% of sites respectively. Combined availability of screening and on‐site management of depression, PTSD, and SUDs, and other mental health disorders was reported by 42%, 14%, 26% and 19% of sites, respectively. On‐site management of depression and PTSD was reported significantly less often in rural as compared to urban settings (depression: 33% and 78% respectively; PTSD: 24% and 58% respectively). Screening for depression and SUDs was least commonly reported by HIV programmes that treated only children as compared to HIV programmes that treated only adults or treated both adults and children. Conclusions: Significant gaps exist in the management of MSDs in HIV care settings in LMICs, particularly in rural settings. Identification and evaluation of optimal implementation strategies to scale and sustain integrated MSDs and HIV care is needed.